Engaging Opportunities and Challenges: Students’ Perspectives Towards Developing Islamic Education Learning Media - Arifah, Mir'atun Nur; Saputra, Kurniawan Dwi; Baharuddin, A Zamakhsyari (EDUKASIA, 2024)
This research explored students’ perspectives regarding the opportunities and challenges in developing Islamic Education learning media. Using a quantitative approach with a survey research design, the study distributed questionnaires to gather data on students' views. The results were further explored and interpreted using semi-structured interviews and observations to enrich the findings and provide deeper insights. The collected data was analyzed to identify patterns and trends in their perspectives. The research found that students viewed the learning media development as supporting accessibility and flexibility, enhancing learning quality, and fostering student potential and motivation. Conversely, students identified inequality in access, teacher roles and challenges, and the quality and usability of digital media as significant obstacles. These findings offered valuable insights for educators and learning developers in designing strategies for integrating digital learning media for Islamic Education. However, this study was limited to student perspectives, and further research involving other stakeholders is recommended to provide a more comprehensive understanding about the topic